DETERMINANTS OF HEPATITIS PREVENTION - Muhammad Imran; Jamal Abdul Nasir; Syed Arif Ahmed Zaidi et al. (Journal of University Medical & Dental College, 2016)
Objective: To assess the socio-demographic factors that has potential influence in the prevention of hepatitis of reproductive age men and women. Methods: Descriptive and inferential analysis carried out. Data: Pakistan Demographic and Health Survey (PDHS) 2012-13. Results: Male has higher (65%) knowledge of hepatitis prevention compared to female (48%).Two multinomial logistic regression models are executed separately for men and women. The models revealed that urban resident has more knowledge about hepatitis prevention compared to rural. Age, education level, access to media and wealth index are positively associated with hepatitis prevention. Being illiterate the likelihood almost double and more than double that the ever married men and women would say that the hepatitis cannot be preventable respectively compared to their counterpart having higher level of education. Ever married men and women who did not access to newspaper [OR=1.95, OR=1.32] and TV [OR=1.46, OR=1.42] were more prone that the hepatitis cannot be preventable compared to those who access to newspaper and TV respectively. Conclusion: Socio-demographic aspects such as age, education, place of residence and access to media TV, radio and newspaper and wealth index are found to be significant. These statistical outcomes can be a useful in anti-hepatitis seeking measures and mechanism.